2019
DOI: 10.1002/ange.201908914
|View full text |Cite
|
Sign up to set email alerts
|

Strukturmodell von Polymermizellen in Abhängigkeit von der Curcumin‐Beladung mithilfe von Festkörper‐NMR‐Spektroskopie

Abstract: Detaillierte Einblickei nd ie Struktur von mit Wirkstoffen beladenen Polymermizellen sind rar,aber wichtig um gezielt optimierte Transportsysteme entwickeln zu kçnnen. Wirk onnten beobachten, dass eine Erhçhung der Curcumin-Beladung von Triblockcopolymeren auf Basis von Poly(2oxazolinen) und Poly(2-oxazinen) schlechtere Auflçsungseigenschaften nachs ich zieht. Mitthilfe von Festkçrper-NMR-Spektroskopie und komplementären Techniken ist es mçglich, ein ladungsabhängiges Strukturmodell auf molekularer Ebene zu er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Very recently, a solid-state NMR study revealed that the high loading of curcumin can be attributed to its interactions with the hydrophilic polymer blocks. [132] A follow-up study reported the self-assembly behavior and in vitro anticancer properties of curcumin loaded PMeOx-PPrOzi-PMeOx micelles. [133] Interestingly, the copolymer itself does not form micelles due to the low hydrophilic/hydrophobic contrast.…”
Section: Elseviermentioning
confidence: 99%
“…Very recently, a solid-state NMR study revealed that the high loading of curcumin can be attributed to its interactions with the hydrophilic polymer blocks. [132] A follow-up study reported the self-assembly behavior and in vitro anticancer properties of curcumin loaded PMeOx-PPrOzi-PMeOx micelles. [133] Interestingly, the copolymer itself does not form micelles due to the low hydrophilic/hydrophobic contrast.…”
Section: Elseviermentioning
confidence: 99%
“…We recently reported that in fact the hydrophilic corona is involved in the binding of CUR in this system. [74] Similar to the incorporation of the neat triblock copolymers, A-BuOx-A/CUR exhibited the highest gel stiffness at a given temperature, whereas G′ of A-PrOzi-A/CUR was still below that of neat H100.…”
Section: Incorporation Of Cur Nanoformulations Of Aba Triblock Copolymentioning
confidence: 89%
“…In particular, amphiphilic triblock copolymers have been reported to exhibit very high drug loading [13][14][15][16] , while recently also gradient copolymer have been suggested [17] . The distinct macromolecular structure of POx and POzi facilitates high drug loading capacities via the high density of tertiary amides along the involvement of the hydrophilic domains of the polymer micelles [18][19][20][21] , addressing one of the critical limitations in MN-based TDDS. Moreover, their inherent stability and biocompatibility underscore their suitability for sustained drug release, ensuring a controlled pharmacological profile while minimizing systemic side effects.…”
Section: Introductionmentioning
confidence: 99%